Chemical vapour deposition growth and Raman characterization of graphene layers and carbon nanotubes. (January 2016) - Lai, Y-C; Rafailov, P M; Vlaikova, E; Marinova, V; Lin, S H; Yu, P; Yu, S-C; Chi, G C; Dimitrov, D; Sveshtarov, P; Mehandjiev, V; Gospodinov, M M
Abstract: Single-layer graphene films were grown by chemical vapour deposition (CVD) on Cu foil. The CVD process was complemented by plasma enhancement to grow also vertically aligned multiwalled carbon nanotubes using Ni nanoparticles as catalyst. The obtained samples were characterized by Raman spectroscopy analysis. Nature of defects in the samples and optimal growth conditions leading to achieve high quality of graphene and carbon nanotubes are discussed.